High density planting system in apple using clonal rootstock: A profitable venture - Kumar, Rajender; Thakur, Himanshu; Singh, Sakshi; Sharma, Nidhi (Indian Horticulture, 2021)
With the reduction in average land holdings, shifting from low density planting systems to high density planting systems is need of the hour, as the trees under these systems are more precocious, heavy yielders and produce better quality fruits. One of the key advantage of these systems is the distribution of light which is equally distributed over the canopy and each fruit gets optimum light for better colour development. It allows most of the work to be done from the ground itself and also gives an opportunity for mechanization which will reduce the amount of labour capital later required.